Social Resistance Strategy of Indigenous Samin Community - Zarkasi, Ibnu Fath; Soedibyo, Desiderius; Haryanti, Rina Herlina; Rahardian, Ramaditya (Magister Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2021)
This study analyzed the culture of the Indigenous peoples, in this case, the Samin community in the Kendeng Mountains of Pati Regency, which has many natural resources, one of which is an excellent limestone for cement companies. In 2014, the Regent of Pati issued a Decree of the Regent of Pati No. 660.1/4767/2014 concerning environmental permits for the construction of cement plants, on the other hand, the communities around the Kendeng mountains that inhabited the area for a dozen years were worried about the plan to build the cement plant that would threaten the ecological balance of the Kendeng Mountains. The purpose of this study is to find out the social resistance strategy of Samin peoples in responding to the policy of cement plant construction. The approach used in this study uses ethnographic studies. Observations were made on the state of the village, physical environment, social facilities, and infrastructure, as well as activities in the community. The findings of the study revealed that this social movement showed the influence of policies desired by the indigenous Samin community, but the policy changes desired by the group still did not produce positive results. On the other hand, Samin peoples can frame this issue into large and national attention.